Analysis of the Elements of Unlawful Acts in Decision Number 34/Pdt.G/2018/PN Bli and the Position of L&B Tax as Evidence - Maharani, Aurelia Gisa; Pongsirinding, Fisa Ande; Putri, Rafirstka Madyah (Dinasti Research, 2025)
In Indonesia, the concept functions to protect the rights of individuals and groups who are harmed by the actions of others. Based on Article 1365 of the Indonesian Civil Code, any unlawful act that causes harm to another party gives rise to the obligation of the perpetrator to compensate for the damage caused. This study examines the application of tort elements in Decision Number 34/Pdt.G/2018/PN Bli, which involved an inheritance land dispute between the plaintiffs and the defendants, with the Head of the Bangli Land Office also joined as a co-defendant. The plaintiffs argued that the disputed land constituted a legitimate inheritance, but they were only able to support their claim through the Land and Building Tax Assessment Notice. Conversely, the defendants succeeded in proving ownership by presenting a Land Ownership Certificate that was procedurally issued by the National Land Agency. In its ruling, the panel of judges rejected the plaintiffs’ main claim and granted the defendants’ counterclaim, declaring that the plaintiffs had committed an unlawful act by occupying the land without a valid legal basis. This judgment emphasizes that the Land and Building Tax Assessment Notice does not have legal force as proof of land ownership, serving merely as an administrative taxation document, whereas the Land Ownership Certificate constitutes valid and strong evidence of ownership in accordance with Article 32 paragraph 1 of Government Regulation No. 24 of 1997 concerning Land Registration. This study highlights the importance of distinguishing between administrative evidence and juridical evidence in land disputes.